2022
DOI: 10.1109/jphot.2022.3164355
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Security Analysis of UAV-Based FSO/CV-QKD System Employing DP-QPSK/CD

Abstract: Unmanned aerial vehicles (UAV) based on free-space optical (FSO) systems combine the benefits of both the high data rate of the FSO and the mobility of UAV. However, cumulative effects of laser beam divergence and turbulence-induced fading on the received irradiance in the FSO link might allow an external eavesdropper located near the authorized receiver to break the transmission under certain conditions. Quantum key distribution (QKD) is a technique of secure communication that employs quantum mechanics-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…In Ref. 89, the performance evaluation is done for UAV based FSO CVQKD systems using dual polarization quadrature phase shift keying with coherent detection. Here, Gaussian modulation of coherent states is employed as it is more effective against collective attacks.…”
Section: Continuous Variable Quantum Key Distributionmentioning
confidence: 99%
“…In Ref. 89, the performance evaluation is done for UAV based FSO CVQKD systems using dual polarization quadrature phase shift keying with coherent detection. Here, Gaussian modulation of coherent states is employed as it is more effective against collective attacks.…”
Section: Continuous Variable Quantum Key Distributionmentioning
confidence: 99%
“…The study concluded that the reason for ECC's success was due to industrial adaptation, which is as important as the performance advantages of a data security proposal. Recently, a non-terrestrial satellite or UAV-based FSO system whilst employing quantum key distribution (QKD) to secure the transmission was proposed in [11,12]. However, quantum-based security is cost ineffective because the technology is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the asymptotic analysis was also provided. In [27], the performance of a UAV-based FSO system employing prepare and measure continuous-variable quantum key distribution (CV-QKD) protocol based on Gaussian modulation of quantum coherent states (GMCS) under collective attacks was investigated in terms of outage probability, quantum bit error rate (QBER), and secret key rate (SKR). In [28] and [29], the authors carried out the comprehensive performance analysis of UAV-based mixed FSO/RF system models for internet of vehicles (IoV) and space ground integrated network (SAGIN) scenarios, respectively.…”
Section: Introductionmentioning
confidence: 99%